TINJAUAN YURIDIS WANPRESTASI TERHADAP PELAKSANAAN PERJANJIAN PEMBIAYAAN KENDARAAN MOBIL TOYOTA PADA PT OTO MULTIARTHA FINANCE PEKANBARU - S, Esrahethi; Hanifah, Mardalena; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Consumer financing is financing activities for the procurement of goods based on the needs of consumers with payment in installments. "One is a consumer finance company PT Oto Multiartha Finance Pekanbaru. Implementation of consumer financing agreement by PT Oto Multiartha Finance Pekanbaru with debtors (customers) create an obligation that must be carried out according the agreement debtor in chapter 10, among others: will not sell, rent, transfer, and do not damage the object of the agreement. In fact the debtor does not meet the achievement, where many of the objects were damaged when the agreement so that the company pulled wansprestasi debtor. Formulation of the problem in this research is how the implementation of consumer financing agreement with PT Oto Multiartha Finance Pekanbaru ?. if the debtor defaults barriers in consumer financing agreement with PT Oto Multiartha Finance Pekanbaru ?. whether the efforts made by PT Oto Multiartha Finance Pekanbaru? This type of research is Juridical Sociological. The nature of this research is descriptive. This research was conducted at PT Oto Multiartha Finance Pekanbar in Jalan HR Soebrantas No. 88 Panam. The conclusion in this study. First, the implementation of consumer financing agreement by PT Oto Multiartha Finance pekanbaru not be separated from the obligation of the debtor, in fact the debtor defaults. Second, the debtor defaults can not be separated from the barriers - barriers such as: accidents. The third attempt was made to withdraw and the debtor is obligated to pay any losses creditors within 14 days. Suggestions author, PT Oto Multiartha be more careful of the characters that will be the consumer. Consumers are aware of their obligations and do not commit acts prohibited by the company. Law on consumer financing more clearly on the rights, obligations, and sanctions against both parties. Keywords: Consumer Finance-Wanprestasi- Withdrawal